Analisis Prosedur Temu Kembali Arsip Inaktif pada Divisi Corporate Secretary PT Taspen (Persero) - Elisabeth Setyani Krismawarti; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2025)
The management of inactive archives is crucial for companies, including PT Dana Tabungan dan Asuransi Pegawai Negeri (TASPEN), which has a large volume of documents. This study aims to understand the procedures for retrieving inactive archives in the Corporate Secretary Division, along with the tools and information systems used. The research employs a descriptive qualitative method through observation, interviews, and documentation. Findings indicate that inactive archives are stored in the Secretariat Department Room for 5 to 10 years. The retrieval procedure involves filling out a request form verified by staff, with search times ranging from 2 to 10 minutes. Challenges include human errors during data input and borrowers forgetting to return archives on time. To address these issues, TASPEN conducts regular training for employees and checks the list of transferred archives. Additionally, TASPEN is innovating by developing an E-Archive system to minimize errors and enhance integrated archive management.